The impact of work-life balance on the quality of life among women employees in UniSZA, Malaysia - Muda, Tengku Fatimah Muliana; Mohd Yusoff, Zurita; Ismail, Siti Khatijah; Syed Husin, Syh Noorul Madihah; Daud, Normadiah; Ab Aziz, Sumayyah; Mohd, Azizah (Allied Business Academies, 2021)
The conflicting demands of work and personal life have always been the attention to many. Striking demographic shifts such as the increasing number of women in the work force, heightening the awareness of work-life issues. In contrast, conflicts between work and personal life priorities can be catalyst for a low quality of life. Thus this study aimed to investigate the impact of work-life balance on the Quality of Life (QoL) among women employees in UniSZA, Malaysia. Quantitative method was employed, whereby data were analyzed using Structural Equation Modeling (SEM) with IBM-SPSS-AMOS program version 21.0. Three dimensions of work-life balance were assessed, Work Interference with Personal Life, Personal Life Interference with Work and Personal Life, and Work/Personal Life Enhancement. The findings revealed that there is direct impact of work-life balance on the quality of life among women employees in UniSZA, Malaysia.